Introduction: Studying Violence in Africa: Contributions from Sources, Fieldwork Challenges and Ethical Considerations - (:unkn) unknown (My University, 2021)
Even since Weber and Durkheim made it a major intellectual topic, violence has been a research object with significant emotional, partisan, and ideological power. Although it increasingly raises questions that concern the human and social sciences in general, the topic simultaneously requires an interrogation of methods and ethics concerning access to fieldwork, the nature of collected sources and the conditions in which they were collected, as well as self-reflexivity on the part of the researcher. Furthermore, the definition of violence as a social fact is relative and subject to debate. It is not enough to rely on an axiological neutrality which, when dealing with violent practices, risks ratifying the erasure of persecutors’ actions and responsibilities (Naepels 2006). Research on violence carries psychological and moral implications, which is why it requires rigour to ensure its legitimacy among the social sciences and humanities and to protect it from any form of voyeurism. One of the most important questions that arises in the analysis of such phenomena, however, is the compatibility between empirical requirements and the physical and psychological integrity of the researcher. This special issue aims at contributing to the important, if not critical, reflection on violence in the humanities and social sciences, on the African continent in particular. For researchers, the concern is indeed not to abandon the research and analyses of violent settings to humanitarian actions and media expertise. Although the term “field” originated from the military vocabulary, meaning a place of tension and conflict (Pulman 1988), we must also consider the risk involving the study of violence in Africa as a challenge or a fascination with exoticised danger, especially when fieldwork in a violent setting is systemically highlighted in spite of physical and psychological risks for the researchers, but also for their assistants and their interlocutors.
Keywords: African Research